Reduction of COPD Hyperinflation by Endobronchial Valves Improves Intercostal Muscle Morphology on Ultrasound - Wallbridge, Peter (Int J Chron Obstruct Pulmon Dis, 2020)
BACKGROUND AND OBJECTIVES: Parasternal intercostal ultrasound morphology reflects spirometric COPD severity. Whether this relates to the systemic nature of COPD or occurs in response to hyperinflation is unknown. We aimed to assess changes in ultrasound parasternal intercostal muscle quantity and quality (echogenicity) in response to relief of hyperinflation. We hypothesised that reduction in hyperinflation following endobronchial valve (EBV) insertion would increase ultrasound parasternal thickness and decrease echogenicity. METHODS: In this prospective cohort study, eight patients with severe COPD underwent evaluation of health-related quality of life, lung function, and sonographic thickness of 2(nd) parasternal intercostal muscles and diaphragm thickness, both before and after EBV insertion. Relationships between physiological and radiographic lung volumes, quality of life and ultrasound parameters were determined. RESULTS: Baseline FEV(1) was 1.02L (SD 0.37) and residual volume (RV) was 202% predicted (SD 41%). Median SGRQ was 63.26 (range 20–70.6). Change in RV (−0.51 ± 0.9L) following EBV-insertion showed a strong negative correlation with change in parasternal thickness (r = −0.883) ipsilateral to EBV insertion, as did change in target lobe volume (−0.89 ± 0.6L) (r = −0.771). Parasternal muscle echogenicity, diaphragm thickness and diaphragm excursion did not significantly change. CONCLUSIONS: Dynamic changes in intercostal muscle thickness on ultrasound measurement occur in response to relief of hyperinflation. We demonstrate linear relationships between intercostal thickness and change in hyperinflation following endobronchial valve insertion. This demonstrates the deleterious effect of hyperinflation on intrinsic inspiratory muscles and provides an additional mechanism for symptomatic response to EBVs.